2018
DOI: 10.1007/s00114-017-1536-7
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal shaving affects concentrations of faecal cortisol metabolites in lactating golden hamsters

Abstract: Breeding of golden hamsters is classically performed at thermal conditions ranging from 20 to 24 °C. However, growing evidence suggests that lactating females suffer from heat stress. We hypothesised that shaving females dorsally to maximise heat dissipation may reduce stress during reproduction. We thus compared faecal cortisol metabolites (FCM) from shaved golden hamster mothers with those from unshaved controls. We observed significantly lower FCM levels in the shaved mothers (F1,22 = 8.69, p = 0.0075) poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Given that pup loss in our study occurred exclusively during the first 24 h after birth, delayed expose to temperature treatments might conceal potential temperature effects on female reproductive investment. Similar to our study, a negative temperature effect was also observed on reproductive parameters in rats kept at 33 °C [ 52 ] and hamsters kept at 30 °C [ 53 , 54 ]. In our study, the best reproductive outcome was found when females were kept at 25 °C, though there was little difference between 20 °C and 25 °C.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Given that pup loss in our study occurred exclusively during the first 24 h after birth, delayed expose to temperature treatments might conceal potential temperature effects on female reproductive investment. Similar to our study, a negative temperature effect was also observed on reproductive parameters in rats kept at 33 °C [ 52 ] and hamsters kept at 30 °C [ 53 , 54 ]. In our study, the best reproductive outcome was found when females were kept at 25 °C, though there was little difference between 20 °C and 25 °C.…”
Section: Discussionsupporting
confidence: 89%
“…Pup body mass is directly related to female body mass since the development of the mammary gland and lactation is dependent on adequate food and water intake. In addition, pup body mass can indirectly be affected by the impact of the ambient temperature on the lactating mother: According to the heat dissipation limit hypothesis, females cannot dissipate enough metabolic heat at higher ambient temperatures and therefore limit milk production, which results in reduced pup weight [ 54 , 59 , 60 , 61 , 62 ]. This hypothesis was critically discussed by Sadowska and coworkers [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed in Speakman and Keijer (2013), this is a very debatable concept and has a huge impact on stress and well-being of the female mothers. In a parallel study, we recently showed that female golden hamsters shaved dorsally in lactation had lower stress than mothers with intact fur (Ohrnberger et al, 2018). In light of our new data on lactation energetics in nursing golden hamsters, we caution against too high maintenance temperatures in breeding golden hamsters in accordance with the lower recommendation for mice (Speakman and Keijer, 2013).…”
Section: Discussion Heat Dissipation Limitation In Lactating Golden Hmentioning
confidence: 84%
“…In contrast to our study with a heat exposure starting at the last third of pregnancy, Zhao and coworkers exposed the females and their litters only from day 6 postpartum to higher temperatures, whereas the pup losses in our study occurred only during the first 24 hours after birth. In rats kept at 33°C [52] and hamsters kept at 30°C [53,54] a negative temperature effect was also observed on reproductive parameters. In our study the best reproductive results were found when females were kept at 25°C, though there was hardly any significant difference between 20°C and 25°C.…”
Section: Discussionmentioning
confidence: 99%